Transcriptional response to West Nile virus infection in the zebra finch (Taeniopygia guttata) - Newhouse, Daniel J.; Hofmeister, Erik K.; Balakrishnan, Christopher N. (My University, 2017)
West Nile virus (WNV) is a widespread arbovirus that imposes a significant cost to both human and wildlife health. WNV exists in a bird-mosquito transmission cycle in which passerine birds act as the primary reservoir host. As a public health concern, the mammalian immune response to WNV has been studied in detail. Little, however, is known about the avian immune response to WNV. Avian taxa show variable susceptibility to WNV and what drives this variation is unknown. Thus, to study the immune response to WNV in birds, we experimentally infected captive zebra finches (Taeniopygia guttata). Zebra finches provide a useful model, as like many natural avian hosts they are moderately susceptible to WNV and thus provide sufficient viremia to infect mosquitoes. We performed RNAseq in spleen tissue during peak viremia to provide an overview of the transcriptional response. In general, we find strong parallels with the mammalian immune response to WNV, including upregulation of five genes in the Rig-I-like receptor signalling pathway, and offer insights into avian-specific responses. Together with complementary immunological assays, we provide a model of the avian immune response to WNV and set the stage for future comparative studies among variably susceptible populations and species.